EFEKTIVITAS PERMAINAN TRADISIONAL JAWA DALAM MENINGKATKAN PENYESUAIAN SOSIAL PADA ANAK USIA 4-5 TAHUN DI KECAMATAN SURUH - Nourovita, Aulia Rifka (Jurusan PGPAUD FIP UNNES, 2013)
Children’s social adjustment ability depends of parenting pattern. Although many parents consider sosial adjustment is unnecessary ability to be concerned. one of the methods to optimalize children’s social adjustment is by playing. One of appropriate games to play is traditional Javanesse game. The game enables children to interact with his friend. The aim of this research is to investigate whether the traditional Javanesse game is able to improve children’s social adjustment in the age 4-5 years old. The method used in this study are experimental research which employed pretest and posttest control design. From the research it can be concluded that traditional Javanese is effective to improve children’s social adjustment on the age 4 to 5 years old. The result can be inferred from the t test of the controlled and experiment group which is 5.056 with ttabel of 2.779. There are minus point in this study caused by lack of time in conducting the research related to permission to do it because the appointed school has its own programme in learning and some subjects of the study at the experiment class did not join the treatment so that the result of this study is not completely maximum. Children’s social adjustment ability depends of parenting pattern. Although many parents consider sosial adjustment is unnecessary ability to be concerned. one of the methods to optimalize children’s social adjustment is by playing. One of appropriate games to play is traditional Javanesse game. The game enables children to interact with his friend. The aim of this research is to investigate whether the traditional Javanesse game is able to improve children’s social adjustment in the age 4-5 years old. The method used in this study are experimental research which employed pretest and posttest control design. From the research it can be concluded that traditional Javanese is effective to improve children’s social adjustment on the age 4 to 5 years old. The result can be inferred from the t test of the controlled and experiment group which is 5.056 with ttabel of 2.779. There are minus point in this study caused by lack of time in conducting the research related to permission to do it because the appointed school has its own programme in learning and some subjects of the study at the experiment class did not join the treatment so that the result of this study is not completely maximum.